2002
DOI: 10.1103/physrevb.65.144106
|View full text |Cite
|
Sign up to set email alerts
|

Very large gold and silver sputtering yields induced by keV to MeV energyAunclusters(n=113

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
72
2
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(82 citation statements)
references
References 27 publications
7
72
2
1
Order By: Relevance
“…(2), the total sputtering yield is found to increase by factors of 4.9 and 10.1 upon switching from mono-to di-and from mono-to triatomic projectiles, respectively. These values compare well with recently measured sputtering yield data for polycrystalline gold and silver targets under bombardment with Au À m projectiles [20,21], where the yield was found to scale with projectile nuclearity as m 2 thus leading to yield enhancement factors of 4 and 9 for m ¼ 2 and 3, respectively. More specifically, if the silver yield data of [21], which have been measured at higher impact energies than employed here, are extrapolated down to 7 keV/atom, one finds enhancement factors of 5 and 10.5 which are in very good agreement with those determined here.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…(2), the total sputtering yield is found to increase by factors of 4.9 and 10.1 upon switching from mono-to di-and from mono-to triatomic projectiles, respectively. These values compare well with recently measured sputtering yield data for polycrystalline gold and silver targets under bombardment with Au À m projectiles [20,21], where the yield was found to scale with projectile nuclearity as m 2 thus leading to yield enhancement factors of 4 and 9 for m ¼ 2 and 3, respectively. More specifically, if the silver yield data of [21], which have been measured at higher impact energies than employed here, are extrapolated down to 7 keV/atom, one finds enhancement factors of 5 and 10.5 which are in very good agreement with those determined here.…”
Section: Resultssupporting
confidence: 87%
“…These values compare well with recently measured sputtering yield data for polycrystalline gold and silver targets under bombardment with Au À m projectiles [20,21], where the yield was found to scale with projectile nuclearity as m 2 thus leading to yield enhancement factors of 4 and 9 for m ¼ 2 and 3, respectively. More specifically, if the silver yield data of [21], which have been measured at higher impact energies than employed here, are extrapolated down to 7 keV/atom, one finds enhancement factors of 5 and 10.5 which are in very good agreement with those determined here. Moreover, somewhat older published yield data for polycrystalline silver under bombardment with Sb þ m projectiles [22], again extrapolated down to 7 keV/ atom, yield enhancement factors of 4.8 and 14.4, which again compare well with the self-sputtering data determined here.…”
Section: Resultssupporting
confidence: 87%
“…Heat spikes can lead to massive sputtering yields by a combination of evaporation and flow of liquid material from the heat spike. 68,120 Low-energy can also sputter material at energies below the physical sputtering threshold via bond-weakening and breaking mechanisms. 121 Well-described examples of this are the so called Küppers cycle, in which ion bombardment weakens chemical bonds so that molecules can then desorb thermally 122 and swift chemical sputtering, in which hydrogen isotopes with energies of the order of 10 eV can break bonds athermally by entering between two atoms.…”
Section: A Production Of Defects In Bulk Targetsmentioning
confidence: 99%
“…Using the semi-empirical theory, Seah [11] showed that for gold using 16 and 64 keV Au primary ions, the predicted yields were 13 and 20 but that, if the theory were extended to include the thermal spike approach of Sigmund and Claussen [12], the values increased to 17 and 40, respectively. Seah's [11] full calculations described the experimental data of Bouneau et al [13] with a standard deviation of 17% for primary ion energies up to 2800 keV, with primary ion clusters up to Au 13 + and yields up to 14313. It is clear that the molecular dynamics simulations, at least for the flat surface, were generating yields that were a factor of 16 ± 3 times too high compared with those at equilibrium and so may also be too high in nanoparticles.…”
mentioning
confidence: 99%